Effects of Implementing Scholastic Literacy Pro, a Program Aimed at Facilitating Independent Reading and Utilizing Data to Tailor Instruction - Arpilled Navarro (AKADEMI SERTIFIKASI PROFESI INTERNASIONAL, 2025)
This study evaluated the reading competence levels of Grade 1 pupils at St. Paul University Surigao utilizing Scholastic Literacy Pro. The research utilized a one-group pretest-posttest methodology to evaluate the effects of Scholastic Literacy Pro, a program aimed at facilitating independent reading and equipping educators with data for personalized instruction. The researchers administered pre- and post-assessments to evaluate the students' advancement in reading competency, classifying their scores into advanced, proficient, basic, and below basic categories. The results indicated that competence levels were primarily below basic, with only a minor minority achieving basic, proficient, or advanced levels. No substantial differences were identified when categorized by section, gender, prior educational institution, or type of school. A notable disparity was observed between pre- and post-test results, signifying that the instructional reading intervention exerted a beneficial effect. The study advocates for targeted instructional strategies to enhance reading proficiency, continuous professional development for teachers on effective methodologies and progress monitoring, and the augmentation of teachers' knowledge and skills to accommodate diverse learner requirements. By adopting these recommendations, the school can further enhance reading competency levels among Grade 1 children.